Reckless eaudiobook - Roberts, Lauren (Powerless Trilogy, 2024)
Paedyn and Kai battle with duty and desire in this highly anticipated second installment in the sizzling and epic romantic fantasy trilogy that's packed with spicy tension and edge-of-your-seat betrayal. The kingdom of Ilya is in turmoil... After surviving the Purging Trials, Ordinary-born Paedyn Gray has killed the King and kickstarted a Resistance throughout the land. Now she's running from the one person she had wanted to run to. Kai Azer is now Ilya's Enforcer, loyal to his brother Kitt, the new King. He has vowed to find Paedyn and bring her to justice. Across the deadly Scorches, and deep into the hostile city of Dor, Kai pursues the one person he wishes he didn't have to. But in a city without Elites, the balance between the hunter and hunted shifts—and the battle between duty and desire is deadly.